BRUGADA PHENOCOPY IN HYPERKALEMIA - A RARE ECG FINDING - Kumar, Nirdosh; Fareed Ahmed,; Areeba Memon,; Jamil Ahmed, (Journal of Ayub Medical College Abbottabad, 2023)
Hyperkalemia is a potentially fatal clinical problem frequently seen in the emergency department (ED). It causes a spectrum of electrocardiogram (ECG) changes such as peaked T-waves, prolonged PR interval, widened QRS complexes, intraventricular/fascicular/bundle branch blocks, etc. Brugada Phenocopy (BrP) is a rare ECG finding seen in severe hyperkalemia associated with the prevalence of malignant cardiac arrhythmias and all-cause mortality. Unlike Brugada Syndrome (BrS) it is a transient phenomenon and completely resolves with the normalization of hyperkalemia. Here we report a Brugada Phenocopy (BrP) case observed in a middle-aged male with severe hyperkalemia.